Analisis Tindak Tutur Deklaratif yang terdapat pada Film "Cek Toko Sebelah" Karya Ernest Prakasa - Sonia Manihuruk; Sihotang, Elsa Septaria; Manalu, Gresia Krisanta; Marbun, Rosliana; Sihite, Visensia; Dinda Nur Maulida; Br Nainggolan, Debora Putriani; Elysabet Br. Zebua; Anggia Puteri (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to describe declarative speech in the film "Check the School Store". The research method used is a qualitative descriptive method. The data source is the speech in the film “Cek Toko Sekolah”. The data collection techniques used were the listening technique, the skill-free listening technique (SBLC), and the note-taking technique. The data analysis used in the research is a pragmatic equivalent method. The results and discussion in this research are, in the entire content of the film "Check the School Store" there are 21 declarative speech sentences. These speech sentences are scenes and characters that use declarative statements to emphasize their position or opinion, thereby strengthening the message they want to convey